Drawing on the dark triad to teach effective leadership is dangerous, irresponsible, and bad theory - Pina e Cunha, M.; Clegg, S.; Rego, A.; Simpson, A. V. (Academy of Management Learning and Education, 2024)
The proposition that the dark triad (DT) personality traits, comprising a callous “constellation” of Machiavellianism, narcissism, and psychopathy, are beneficial for leaders has gained traction. While supported by certain scholars and practitioners, this perspective represents bad management theory that undermines good management practice. Although some research has suggested potential benefits of DT traits in leaders, it is a mistake to assume that the traits are inherently functional. A common error underlying this viewpoint is the assumption that if a number of successful and celebrated leaders exhibit DT behaviors in their leadership, then other managers must adopt similar behaviors to be effective and successful. In this essay, we propose a teaching–learning agenda aimed at identifying and screening dark traits, reducing DT behaviors in future leaders, and dealing with DT leaders. Just as good educators combat toxic management behaviors that hinder sustainability, we should also counteract toxic management behaviors that negatively affect employees, organizations, and even society. Despite the apparent correlation with stereotypes of successful leaders, DT traits in leadership are a destructive force, and it is important to teach students and practitioners how to counteract them.